The description of a new brackish water ciliate species from China, Trachelostyla aestuarina n. sp., with a species key and biogeographic investigation for Trachelostyla (Ciliophora, Sporadotrichida) - Zhang, Zihui; Hines, Hunter N.; Pan, Hongbo; Jiang, Jiamei (Frontiers in Marine Science, 2022)
The ciliated protists are a diverse group of microbial eukaryotes that play an important role in the functioning of microbial food webs. The genus Trachelostyla Borror, 1972, comprised a few species with a non-twisted distinctly cephalized shape. The overall taxonomy has been challenging for this group, and the understanding of their diversity and distribution is therefore relatively limited. To further investigate this group, we report here on two species from the East China Sea, Trachelostyla aestuarina n. sp. and Trachelostyla caudata Borror, 1972, including their in vivo morphology, infraciliature, and phylogenetic relationships based on 18S rRNA gene sequences. The physiological reorganization stages of the latter were also investigated. T. aestuarina is characterized by a combination of features including a bipartite cell shape, a size of 150–220 × 15–35 μm, scattered cortical granules, and multiple macronuclear nodules (37–55). T. caudata has only 10 cirri in the frontal region, fewer than its congeners; thus, we improved the definition of the genus. The global distribution of Trachelostyla was summarized based on the available literature and a key to the valid species provided. This work improves the overall knowledge of hypotrich biodiversity and provides underpinning for future researchers in global regions for environmental monitoring and resource investigations.